Synthesis and Oral Hypoglycemic Activity of 3-[5'-Methyl-2'-aryl-3'-(thiazol-2ʺ-yl amino) thiazolidin-4'-one]coumarin Derivatives - Deepthi Kini; Manjunath Ghate (E-Journal of Chemistry)
Number of heterocyclic compounds has been exploited to develop pharmaceutically important molecules, out of which biheterocyclic coumarins are clinically used potential drug candidates showing oral hypoglycemic and antidiabetic activities. A new series of 3-[5'-methyl-2'-aryl-3'-(thiazol-2ʺ-yl amino)thiazolidin-4'-one]coumarin derivatives were designed and synthesized. The title compounds were synthesized from starting material 3- acetyl coumarin. All the synthesized compounds were characterized and screened for hypoglycemic activity. Some of the compounds exhibited promising activity.